Three-dimensional analysis of the take-off preparatory motion in the long jump - Shimizu, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate three-dimensionally how long jumpers move during the take-off preparatory phase and what causes the lateral lean of the body of the touchdown. The subjects were six male university long jumpers. Three-dimensional coordinates and ground reaction forces (GRF) were collected by Vicon cameras and a force platform. The long jumpers placed support foot in the lateral position at L2on and Llon. The take-off foot nearly under the center of mass (COM) in the take-off phase resulted in the inward lean of the take-off leg and the outward lean of the trunk at the instant of touchdown of take-off foot. The lateral lean of the body helped to lower the COM at the touchdown of take-off foot and to use the hip abductors during the take-off-phase.